Application of pectin hydrolyzing bacteria in tobacco to improve flue-cured tobacco quality - Weng, Shuning; Deng, Meizhong; Chen, Shanyi; Yang, Renqiang; Li, Jingjing; Zhao, Xianbo; Ji, Shunhua; Wu, Lixiang; Ni, Li; Zhang, Enren; Wang, Chaochao; Qi, Lingfeng; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
To study the relationship between the diversity of the surface microbial community and tobacco flavor, and to improve tobacco quality using microorganisms. The microbial community composition and diversity of 14 samples of flue-cured tobacco from tobacco-producing areas in Yunnan with varying grades were analyzed by high-throughput sequencing. PICRUSt was used for predicting microbial functions. A strain of Bacillus amyloliquefaciens W6-2 with the ability to degrade pectin was screened from the surface of flued-cured tobacco leaves from Yunnan reroasted tobacco leave.The enzyme preparation was prepared through fermentation and then applied for treating flue-cured tobacco. The improvement effect was evaluated by measuring the content of macromolecule and the changes in volatile components, combined with sensory evaluations. The bacterial communities on the surface of flue-cured tobacco exhibited functional diversity, consisting primarily of Variovorax, Pseudomonas, Sphingomonas, Burkholderia, and Bacillus. These bacterial strains played a role in the aging process of flue-cured tobacco leaves by participating in amino acid metabolism and carbohydrate metabolism. These metabolic activity converted complex macromolecules into smaller molecular compounds, ultimately influence the smoking quality and burning characteristics of fluecured tobacco. The pectinase preparation produced through fermentation using W6-2 has been found to enhance the aroma and sweetness of flue-cured tobacco, leading to improved aroma, reduced impurities, and enhanced smoothness. Additionally, the levels of pectin, cellulose, and hemicellulose decreased, while the levels of water-soluble sugar and reducing sugar increased, and the contents of esters, ketones, and aldehydes increased, and the contents of benzoic acid decreased. The study revealed the correlation between surface microorganisms and volatile components of Yunnan tobacco leaves, and the enzyme produced by the pectin-degrading bacteria W6-2 effectively improved the quality of flue-cured tobacco.